Entrepreneurship and disability. Socio-labour contextualization and employment policies - García Palma, Belén; Manzanera-Román, Salvador; Ortiz García, Pilar (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
This work is part of the R + D + i project of the Ministry of Economy and Competitiveness of Spain, Disability and entrepreneurship. Competence analysis CSO2016-75818-R whose main objective is to know the role played by the knowledge, skills and abilities of people with physical and / or sensorial disabilities in order to explain their entrepreneurial actions. Because of the project has started recently, there are other specific goals: firstly, the socio-demographic analysis of disabled people; secondly, to know their position in the labour market; and finally, the analysis of the role of active labour market policies to overcome the barriers that disabled people have to engage a business. Methodologically, this research is twofold, both quantitative and qualitative. However, in the preliminary phase it has been limited to documentary review and statistic analysis from secondary sources such as Employment of People with Disability, Salary of People with Disability or Living Conditions Survey, among others. The study of entrepreneurship of people with disability shows the peculiarities of this phenomenon in such heterogeneous social group. According to the data used in this research –the majority published in 2015 but refered to 2014–, people with disability is the 4.4% of total population. The 57% of disabled people are men and 43% are women, both concentrated mainly in a 45-64 age group (55.6% of the total) and with a predominant degree of disability in the 33%-44% stretch. On the other hand, the disabilities related to the osteoarticular system (23.7%) represent a significant proportion. People with disabilities are in an unfavorable position to get a job. The employment rate of persons with disabilities accounts for approximately one third of that represented by the non-disabled. Considering the professional situation, people with disabilities are mostly salaried and only 11% work on their own. Its temporary rate is high and by sectors, services account for the highest percentage of employment in this group, especially in tasks of medium and low qualification. The unemployment rate of people with disability is 10% higher than the same rate of people without disability. Besides, there has been a significant drop in the gross annual salary of people with disability in the economic crisis, which has widened the salarial gap between people with and without disability. The situation of the people with disability has been damaged by the economic crisis, which has its reflect in the increase of the percentage of these people in severe exclusion. This fact imposes the need to promote inclusion and activation measures by all social agents. Some studies such as Mercado García, Aizpurúa González and García Vicente (2013) indicate the existence of barriers in the sociallabour inclusion of people with disabilities that have already been mentioned as the lower educational level or the professional qualification far from the real demand of the labour market; nevertheless, the barrier set in the very development of passive policies that persuade the development of a labour alternative is striking. In line with this, Moreno Rodríguez and Tejada Cruz (2015) consider the lack of involvement of public authorities in the promotion of entrepreneurship as a barrier to the entrepreneurship of people with disabilities. Therefore, it is noteworthy that specific programs of active employment policies aimed at promoting the entrepreneurship of people with disabilities are not noticed, although many are already beneficiaries of general entrepreneurship programs. In this context, and beyond the political discourse used by institutional authorities, it is needed an exercise of sensitization and visualization of this social group in front of the society. So, it is important to take measures and specific actions that emphasize their contribution and favour their social-labour inclusion.